2017
DOI: 10.3390/plants6020017
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Grain Preservation and Fertility in Valuable Commercial Rose Cultivars

Abstract: In the cut flower market, traditional breeding is still the best way to achieve new rose cultivars. The geographical delocalization of cultivar constitution (generally made in Europe and North America) and plant cultivation (large areas in Africa and South America) represents a limit point for crossing and selection. Rose breeders often need to overcome geographical distances, resulting in asynchrony in flowering among crossing parents, by storing and sending pollen. Hence, a key aspect in breeding programs is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…The variation in the pollen grain size may result from the pollination and habitat conditions, whereas the pollen grain transport conditions have been found to play a negligible role in the evolution of the pollen size in species pollinated by bees and birds. The change in the grain size has been shown to influence pollen germination, pollen tube growth, and fertilization [ 107 , 108 ]. The pollen grain size may be modified by the content of nitrogen and phosphorus in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in the pollen grain size may result from the pollination and habitat conditions, whereas the pollen grain transport conditions have been found to play a negligible role in the evolution of the pollen size in species pollinated by bees and birds. The change in the grain size has been shown to influence pollen germination, pollen tube growth, and fertilization [ 107 , 108 ]. The pollen grain size may be modified by the content of nitrogen and phosphorus in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of pollen grains can be affected by different factors, extrinsic or intrinsic, in a variable way depending on the plant studied. Some studies have shown that environmental conditions during floral development can influence pollen grain fertility in different ways (Giovannini et al, 2017;Müller et al, 2016). Other studies have shown that factors related to the in vitro culture medium can affect pollen germination (Flores-Rentería et al, 2018;Impe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment on rose species; it was proven that cryostored pollen maintained its fertilization ability and produced seeds [19]. The study on frozen pollen stored among one year demonstrated that pollen stored at low temperatures sustained its original viability and fertility capacity so it was said that pollen storage is a useful tool for breeders [20]. Another research on Carica papaya L. "Washington" pollen which was freeze-dried and stored at −20˚C for 14 months showed that artificial pollination using stored pollen produced fruit set [21].…”
Section: Introductionmentioning
confidence: 99%